REPRESENTING THE PAST THROUGH THE MAGIC OF MINIATURES - Mențeanu, Andrei (Design/Arts/Culture, 2023)
The visual magic of the miniature world allows the depiction of the past using a combination of advanced contemporary, as well as classical technologies. For the viewer to be transported back in time, the miniature must be a hyper-realistic representation that acts on the viewer’s memory and imagination. A miniature, appreciable in size, in which the scenes turn out to be drawn from the reality of the past, constitutes an extremely effective method of actualizing a tragic episode of history. And since miniatures can transform reality into art, they are, simultaneously, artistic compositions.